Afghan Frontier : At the Crossroads of Conflict - Schofield, Victoria (London Tauris Parke Paperbacks, 2010)
The borderlands of Afghanistan and Pakistan have become the arena for a global conflict with consequences that defy prediction. At the crossroads of Central Asia, gateway to India and the West, Afghanistan has tempted countless invaders in their quest for domination. This title traces the history of this region.
Include Illustrations and Index
Keywords: Afghanistan -- Pakistan--Khyber Pakhtunkhwa -- Social conditions